2020
DOI: 10.3390/nu12061827
|View full text |Cite
|
Sign up to set email alerts
|

Links between Nutrition, Infectious Diseases, and Microbiota: Emerging Technologies and Opportunities for Human-Focused Research

Abstract: The interaction between nutrition and human infectious diseases has always been recognized. With the emergence of molecular tools and post-genomics, high-resolution sequencing technologies, the gut microbiota has been emerging as a key moderator in the complex interplay between nutrients, human body, and infections. Much of the host–microbial and nutrition research is currently based on animals or simplistic in vitro models. Although traditional in vivo and in vitro models have helped to develop mechanistic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 249 publications
0
18
0
Order By: Relevance
“…In the era before antibiotics, the diet was a vital part of controlling infections [ 161 ]. Malnutrition, including undernutrition and overnutrition, can increase sensitivity to infectious diseases and magnify the infection severity, which can worsen by malnutrition; the gut microbiota has been attracting interest as an essential mediator in the complex relationships linking food, the human body, and infectious diseases [ 162 ].…”
Section: Vaginal Microbiome Nutrients and Female Reproductive Tract Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the era before antibiotics, the diet was a vital part of controlling infections [ 161 ]. Malnutrition, including undernutrition and overnutrition, can increase sensitivity to infectious diseases and magnify the infection severity, which can worsen by malnutrition; the gut microbiota has been attracting interest as an essential mediator in the complex relationships linking food, the human body, and infectious diseases [ 162 ].…”
Section: Vaginal Microbiome Nutrients and Female Reproductive Tract Infectionsmentioning
confidence: 99%
“…BV is considered a risk factor for several common sexual transmitted infections [ 171 ], including those induced by the bacteria Neisseria gonorrhea, CT, and Mycoplasma genitalium; the protozoan Trichomonas vaginalis; and viruses such as HIV, human papillomavirus (HPV), and herpes simplex virus type 2 (HSV-2) [ 158 , 169 , 170 ]. Many data have reported the relationship between diet and nutritional status in BV, but the mechanism is still unclear [ 162 , 172 ]. Many studies have found associations between BV and low micronutrient status, including vitamins A, C, E, and D and β-carotene, and low dietary intake of folate and calcium [ 162 , 170 , 172 , 173 , 174 ].…”
Section: Vaginal Microbiome Nutrients and Female Reproductive Tract Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“… Use experimental models relevant to the concept of molecular dialogue to unveil the respective role of microbiota and/or immune cells in the production of specific metabolites of interest. In a context where the microbial and host metabolite relationships are not elucidated, this first work consists of a detailed experimental design, followed by a fundamental study on metabolites using specific pathological models (KO mice, mono-colonization of the microbiota with certain strains, synthetic biology strategy, GF and specific pathogen-free model, wilding mice [ 333 ], culturomic, metabolomic model with minimal microbiota, (reviewed in [ 334 ]) and in vitro models [ 335 , 336 ]. …”
Section: Challenges and Perspectives: How To Hear The Sound From Metabolite-mediated Microbiota-host Immunity Crosstalkmentioning
confidence: 99%
“…However, studies using cell lines or animal models to study gut microbiota have their own limitations. Casotta et al, 2020 showed that findings from animal models and cell cultures do not represent and are not translatable to humans [45]. The main limitation of in vivo studies is due to the host's tolerance of microbial infections, which varies greatly across different species [46].…”
Section: Introductionmentioning
confidence: 99%